DETERMINAN KEJADIAN ANEMIA PADA IBU HAMIL - Prabu Aji, Sulistyani; Wulansari, Wulansari; Nur Dewi Kartikasari, M.; Jutomo, Lèwi; Milawati Ramli, Ramlah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Anemia during pregnancy is a condition where the hemoglobin (Hb) value of pregnant women is lower during the first to third trimester of pregnancy. Judging from the data from the Pekanbaru City Health Office in 2020 the highest incidence of anemia in pregnant women was found at the Sidomulyo Pekanbaru Inpatient Health Center, which was 39.1%. Due to the many problems of anemia in pregnant women, the purpose of this study was to determine the factors that influence the incidence of anemia in pregnant women at the Sidomulyo Inpatient Health Center. This type of research is a quantitative study with a cross-sectional design. Data sources in this study are divided into 2, namely primary data sources and secondary data sources. The primary data is all pregnant women at the Sidomulyo Health Center, and the secondary data is in the form of a research questionnaire. Data processing techniques include reduction (data verification), coding (coding), data entry (computerized), cleaning (cleaning) and data aggregation. and use the validity test. The results of this study indicate that the frequency distribution of the characteristics of respondents based on the category of anemia shows that the most categories are not at risk (moderate anemia 7-8.9) as many as 25 respondents with a percentage reaching 69.4% while at risk (mild anemia 9-10.9 ) as many as 11 respondents with a percentage of 30.6%. There is a relationship between age and parity on the incidence of anemia in pregnant women in the working area of Puskesmas RI Sidomulyo.Keywords: Anemia, Hemoglobin, Pregnancy, Pregnant Women.